2006
DOI: 10.1167/6.9.12
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearities in color coding: Compensating color appearance for the eye's spectral sensitivity

Abstract: Most wavelengths change hue when mixed with white light. These changes, known as the Abney effect, have been extensively studied to characterize nonlinearities in the neural coding of color, but their potential function remains obscure. We measured the Abney effect in a new way--by varying the bandwidth of the spectrum rather than mixing with white--and this leads to a new interpretation of the role of nonlinear responses in color appearance. Because of the eye's limited spectral sensitivity, increasing the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 36 publications
4
35
1
Order By: Relevance
“…Salient features of color appearance may also reflect important characteristics of the environment, though somewhat paradoxically, they are not predicted from visual sensitivity, even though sensitivity itself is assumed to be matched to the environment. For example, the colors that appear as perceptual nulls (such as unique yellow which is the null for red vs. green sensations) do not represent the null points of the opponent channels mediating color coding at early post-receptoral levels of the visual system (Krauskopf et al 1982), nor are they tied to individual differences in spectral sensitivity (Schefrin and Werner 1990;Miyahara et al 1998;Brainard et al 2000;Webster et al 2000;Mizokami et al 2006). This has suggested that the unique hues appear special because they represent special features of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Salient features of color appearance may also reflect important characteristics of the environment, though somewhat paradoxically, they are not predicted from visual sensitivity, even though sensitivity itself is assumed to be matched to the environment. For example, the colors that appear as perceptual nulls (such as unique yellow which is the null for red vs. green sensations) do not represent the null points of the opponent channels mediating color coding at early post-receptoral levels of the visual system (Krauskopf et al 1982), nor are they tied to individual differences in spectral sensitivity (Schefrin and Werner 1990;Miyahara et al 1998;Brainard et al 2000;Webster et al 2000;Mizokami et al 2006). This has suggested that the unique hues appear special because they represent special features of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested recently that the visual system uses nonlinear processing of colour information to compensate for its limited spectral responsivity and to assign hues according to the properties of the physical environment rather then mere physiological receptor responses. 30 It is possible that understanding of the functional purpose of this mechanism will lead to new possibilities of accounting for it in colorimetry and colour reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when tested in laboratory settings, failures in hue judgments can arise due to violations in the assumption of natural spectral properties. Recently, Mizokami et al 2 have suggested such an explanation for the failure to predict the hues of spectrally narrow band lights that have been desaturated by the addition of a broad-band white light. When white light is added to a wavelength the perceived hue changes, a classic phenomenon in color appearance known as the Abney effect.…”
Section: Need For Spectrum Shapingmentioning
confidence: 99%
“…These hue shifts reflect a nonlinearity in color appearance, because constant hues do not correspond to constant relative outputs in the cone receptors and thus do not fall along straight lines in color space. However, Mizokami et al 2 suggested that the loci of constant hues could reflect an attempt by the visual system to correct for its own spectral filtering characteristics, so that perceived hue is tied to a consistent property of the stimulus rather than a consistent property of the neural response. Specifically, they suggested that perceived hue might correspond to the inferred peak or modal value of the spectral distribution.…”
Section: Need For Spectrum Shapingmentioning
confidence: 99%
See 1 more Smart Citation